Outcomes of curative-intent treatment for breast cancer patients presenting with sternal or mediastinal involvement - Christopherson, Kaitlin (Int J Radiat Oncol Biol Phys, 2019)
PURPOSE: Optimal treatment of patients diagnosed with de novo metastatic breast cancer limited to the mediastinum or sternum has never been delineated. Herein the authors sought to determine the efficacy of multimodality treatment, including metastasis-directed radiotherapy (RT), in curing patients with this presentation. METHODS AND MATERIALS: This is a single institution retrospective cohort study of de novo metastatic breast cancer patients treated from 2005 – 2014, with a 50 month median follow up for the primary cohort. The primary patient cohort had metastasis limited to the mediastinum/sternum treated with curative intent (n=35). We also included a cohort of patients with stage IIIC disease treated with curative intent (n=244). Additional groups included a mediastinal/sternal palliative cohort (treatment did not include metastasis-directed RT) (n=14), and all other patients with de novo stage IV disease/palliative cohort (n=1185). The primary study outcomes included local-regional recurrence-free, recurrence-free, and overall survival (LRRFS/RFS/OS), calculated using the Kaplan-Meier method. Cox multivariable models compared survival outcomes across treatment cohorts adjusted for molecular subtype, age, and race. RESULTS: For the mediastinal/sternal curative-intent cohort, five-year LRRFS was 85%, RFS was 52%, and OS was 63%. After adjustment, there was no statistically significant difference in LRRFS (HR=0.39; 95% CI 0.13-1.13; P=0.08), RFS (HR=0.87; 95% CI 0.50-1.49; P=0.61), or OS (HR=0.79; 95% CI 0.44-1.43; P=0.44) between the stage IIIC cohort and the mediastinal/sternal curative-intent cohort (referent). In contrast, RFS was worse for the mediastinal/sternal palliative cohort (HR=2.29; 95% CI 1.05-5.00; P=0.04). Overall survival was worst for the de novo stage IV palliative cohort (HR=2.61; 95% CI 1.50-4.53; P<0.001). CONCLUSIONS: For select patients presenting with breast cancer metastatic to the sternum and/or mediastinum, curative-intent treatment with chemotherapy, surgery, and radiation yields outcomes similar to stage IIIC disease and superior to de novo stage IV breast cancer treated with palliative intent.